Modeling and Simulation of Acetaminophen Pharmacokinetics and Hepatic Biomarkers After Overdoses of Extended‐Release and Immediate‐Release Formulations in Healthy Adults Using the Quantitative Systems Toxicology Software Platform DILIsym - James J. Beaudoin; Kyunghee Yang; Brett A. Howell; Zackary Kenz; Vinal V. Lakhani; Jeffrey L. Woodhead; John C. K. Lai; Cathy K. Gelotte; Sury Sista; Evren Atillasoy (CPT: Pharmacometrics & Systems Pharmacology)
ABSTRACT Acetaminophen (APAP) has been formulated as immediate‐, modified‐, and extended‐release tablets (APAP‐IR, ‐MR, and ‐ER, respectively). However, there was concern that APAP‐MR previously available in Europe could form a bezoar after a large overdose, leading to delayed absorption and atypical pharmacokinetics (PK) compared to APAP‐IR, and that current treatment guidelines developed for APAP overdose to prevent severe hepatotoxicity are inappropriate for APAP‐MR. In contrast, APAP‐ER caplets available in the United States are designed with an IR layer and an erodible ER layer. Using modeling and simulation, predicted PK and hepatotoxicity biomarkers following various acute overdose and repeated supratherapeutic ingestion (RSTI) scenarios with APAP‐IR and APAP‐ER were compared to investigate the differences between these two formulations. The existing APAP‐IR representation within DILIsym v8A, a quantitative systems toxicology model of drug‐induced liver injury, was updated, and an APAP‐ER model was developed, using newly acquired in vitro (e.g., tiny‐TIMsg) and clinical data. The model and simulated populations (SimPops) representing healthy adults were extensively validated, before simulating PK and three clinically useful hepatic biomarkers after various overdose scenarios. On average, APAP exposure after acute overdose and RSTI in healthy adults was predicted to be slightly lower for APAP‐ER compared to APAP‐IR, partially due to lower APAP absorption for APAP‐ER, while not markedly impacting the expected time course of APAP plasma concentrations. Similar hepatic biomarker profiles were predicted for both APAP formulations. Based on these results, the APAP overdose consensus treatment guidelines updated in 2023 are not further impacted by this report.